Amphiphilic Poly-N-vinylpyrrolidone Nanoparticles as Carriers for Nonsteroidal, Anti-Inflammatory Drugs: Pharmacokinetic, Anti-Inflammatory, and Ulcerogenic Activity Study - Andrey Kuskov; Dragana Nikitovic; Aikaterini Berdiaki; Mikhail Shtilman; Aristidis Tsatsakis (MDPI AG, 2022)
Nanoparticles are increasingly utilized as drug delivery agents. Previously, we have developed a drug delivery system based on amphiphilic derivatives of poly-N-vinylpyrrolidone (PVP-OD4000) with excellent biocompatibility. In the current study, we assessed the pharmacokinetics, anti-inflammatory profile, and ulcerogenic potential of indomethacin (IMC)-loaded PVP-OD4000 nanoparticles compared to the free drug. Wistar male rats were utilized for a pharmacokinetics study and an anti-inflammatory study. Loaded IMC exhibited a slower elimination rate (p < 0.05) and a higher blood plasma concentration at 8 and 24 h after intraperitoneal injection compared with free IMC. In addition, decreased uptake of loaded IMC in the liver and kidney compared to free IMC (p < 0.05) was detected. Furthermore, PVP-OD4000 nanoparticles loaded with IMC showed an enhanced anti-inflammatory effect compared to free IMC (p < 0.05) in carrageenan-induced and complete Freund's adjuvant-induced-(CFA) sub-chronic and chronic paw edema treatment (p < 0.01; p < 0.01). Notably, upon oral administration of loaded IMC, animals had a significantly lower ulcer score and Paul's Index (3.9) compared to the free drug (p < 0.05). The obtained results suggest that IMC loaded to PVP nanoparticles exhibit superior anti-inflammatory activity in vivo and a safe gastrointestinal profile and pose a therapeutic alternative for the currently available NSAIDs' administration.